Vaginal microbiota associated with oncogenic HPV in a cohort of HPV-vaccinated women living with HIV. (August 2022) - McClymont, Elisabeth; Albert, Arianne Y; Wang, Christine; Dos Santos, Scott J; Coutlée, François; Lee, Marette; Walmsley, Sharon; Lipsky, Nancy; Loutfy, Mona; Trottier, Sylvie; Smaill, Fiona; Klein, Marina B; et al.
Background: Women living with HIV (WLWH) experience higher rates of human papillomavirus (HPV) infection and cervical cancer than women without HIV. Changes in the vaginal microbiome have been implicated in HPV-related disease processes such as persistence of high-risk HPV infection but this has not been well defined in a population living with HIV. Methods: Four hundred and 20 girls and WLWH, age ≥9, across 14 clinical sites in Canada were enrolled to receive three doses of quadrivalent HPV vaccine for assessment of vaccine immunogenicity. Blood, cervical cytology, and cervico-vaginal swabs were collected. Cervico-vaginal samples were tested for HPV DNA and underwent microbiota sequencing. Results: Principal component analysis (PCA) and hierarchical clustering generated community state types (CSTs). Relationships between taxa and CSTs with HPV infection were examined using mixed-effects logistic regressions, Poisson regressions, or generalized linear mixed-effects models, as appropriate. Three hundred and fifty-six cervico-vaginal microbiota samples from 172 women were sequenced. Human papillomavirus DNA was detected in 211 (59%) samples; 110 (31%) contained oncogenic HPV. Sixty-five samples (18%) were taken concurrently with incident oncogenic HPV infection and 56 (16%) were collected from women with concurrent persistent oncogenic HPV infection. Conclusions: No significant associations between taxa, CST, or microbial diversity and HPV-related outcomes were found. However, we observed weak associations between a dysbiotic microbiome and specific species, including Gardnerella, Porphyromonas, and Prevotella species, with incident HPV infection.